Informação & Sociedade: Estudos Vol. 21, n. 1 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
Acesso ao númerohttp://www.ies.ufpb.br/ojs2/index.php/ies/issue/view/824/showToc